Service quality and customer satisfaction among foreign customers towards PNB Darby Park Hotel / Nor Fadillah Fuad - Fuad, Nor Fadillah (Faculty of Business and Management, 2011)
The study was conduct to examine the level of customer satisfaction based on the service quality that provide by the PNB Darby Park Hotel. The sample of 50 questionnaires gathered from the foreign customers using the service that provide by Darby Park. The outcomes of data analysis answer the research objective which is firstly is to identify the level of customers’ satisfaction on PNB Darby Park Hotel. Secondly is to identify the relationship between independent variable and dependent variable. Thirdly is to identify which service quality attribute in the most important. Lastly is to give recommendation to PNB Darby Park Hotel in improving its services. Descriptive research has been adopted for this study. Questionnaires and secondary data including journals, internet and brochures are used for data collection. 50 questionnaires were distributed to the respondents which are foreign customers who are using the service provided by the Darby Park Hotel. The findings showed that the most of the customers are satisfied with the service provided and service quality dimension seems to have influence with customer satisfaction. Recommendations are put on how to improve and increase customer’s satisfaction on the service provided by Darby Park.